The Effect of Damping Terms on Decay Rate for System of Three Nonlinear Wave Equations with Weak-Memories - Guidad, Derradji; Zennir, Khaled; Berkane, Abdelhak; Berbiche, Mohamed (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we consider a very important problem from the point of view of application in sciences and engineering. A system of three wave equations having a different damping effects in an unbounded domain with strong external forces. Using the Faedo-Galerkin method and some energy estimates, we will prove the existence of global solution in R^n owing to to the weighted function. By imposing a new appropriate conditions, which are not used in the literature, with the help of some special estimates and generalized Poincar\’e’s inequality, we obtain an unusual decay rate for the energy function.